Modeling the Internalization of Religious Moderation Values Among Students - Hidayat, Nur; Hidayaturrahman, M.; Hidayat, Wildan Nur; Meilinda, Fitria (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to construct and validate a comprehensive structural model for the internalization of religious moderation values among students within the Islamic Religious Education (PAI) Study Program at UIN Fatmawati Sukarno Bengkulu. Amidst the escalating global and local challenges of ideological polarization, this research addresses a critical gap in the current literature, which has predominantly relied on qualitative-descriptive approaches that fail to elucidate the complex structural mechanisms of value absorption. By adopting a quantitative causal-correlational design, data were systematically gathered from a representative sample of PAI students through stratified random sampling. The data were subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), a robust method for evaluating complex path relationships. The results demonstrate that the measurement model is statistically rigorous, with all latent constructs meeting the stringent validity and reliability thresholds required for structural analysis. The structural model evaluation confirms that the academic environment, religious parenting styles, and religious digital literacy serve as significant exogenous determinants that influence the internalization process. Crucially, value internalization was identified as a substantial mediator for religious moderation behavior, with the integrated independent variables demonstrating a high explanatory capacity for the variance in student behavioral outcomes. The core novelty of this research lies in the empirical validation of the "internalization bridge" conceptualized through the stages of transformation, transaction, and trans-internalization as the pivotal mechanism that converts external environmental and familial influences into consistent, lived behavior. These findings suggest that fostering sustainable religious moderation in higher education necessitates a strategic shift from superficial, ceremonial programming toward a structured, identity-building process that prioritizes the deep psychological and pedagogical internalization of wasathiyyah values.